PERUBAHAN ORGANISASI DAN KOMITMEN KARYAWAN DI UNIVERSITAS MUHAMMADIYAH SUKABUMI (UMMI) - Samsudin, Acep (JURNAL PERSPEKTIF BISNIS, 2013)
This research is to find out the relation between organizational change and commitment against the organization. Cope with the organizational change is an effort by the employee to face the work situation changes. Employee commitment is individual identification and their participation in the process of achieving organizational goals. This research uses incidental sampling technique. The data collected was analyzed by partial correlation. The results showed that 1) there is a significant and positive relation between organizational change and employee 2) there is a positive connotation between long working experience and commitment to the organization. It could be concluded that the better cope with organizational change, the higher employee commitment.Keywords:Organizational Change, Commitment